2011
DOI: 10.1007/s00125-011-2323-1
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-terminal hydrolase L1 is required for pancreatic beta cell survival and function in lipotoxic conditions

Abstract: Aims/hypothesis Ubiquitin C-terminal hydrolase L1 (UCHL1) is associated with neurodegenerative diseases and has been suggested to have roles in pancreatic beta cells. Our proteomic analysis revealed that UCHL1 was the most increased protein in MIN6 cells exposed to palmitate. The present study used a genetic loss-of-function model to test the hypothesis that UCHL1 is required for normal beta cell function and fate under lipotoxic conditions. Methods Human islets, mouse islets and MIN6 cells were used to analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
(81 reference statements)
0
20
0
2
Order By: Relevance
“…-/ -mice as well (Chu et al, 2012). These data suggest that UCHL1 has essential functional and antiapoptotic roles in beta cells under lipid stress, highlighting a novel understanding of the importance of UCHL1 and the ubiquitin proteasome system in the pathobiology of lipotoxicity and T2DM.…”
Section: Ubiquitin C-terminal Hydrolase Lmentioning
confidence: 68%
See 1 more Smart Citation
“…-/ -mice as well (Chu et al, 2012). These data suggest that UCHL1 has essential functional and antiapoptotic roles in beta cells under lipid stress, highlighting a novel understanding of the importance of UCHL1 and the ubiquitin proteasome system in the pathobiology of lipotoxicity and T2DM.…”
Section: Ubiquitin C-terminal Hydrolase Lmentioning
confidence: 68%
“…UCHL1 was identified in a proteomic screen as the most upregulated protein in MIN6 beta cells treated with palmitate (Chu et al, 2012). In this study, Chu et al used a genetic loss-of-function model to test the hypothesis that UCHL1 was required for normal beta-cell function and fate under lipotoxic conditions and it was found that a 4-week high-fat (HFa) diet caused glucose intolerance and impaired insulin secretion in UCHL1…”
Section: Ubiquitin C-terminal Hydrolase Lmentioning
confidence: 99%
“…Studies by our group and others have also focused on the role of ER and cytosolic Ca 2+ dynamics in bcell survival and function upon the initiation of the intrinsic apoptotic pathway (Dror et al, 2008;Gwiazda et al, 2009;Luciani et al, 2009;Varadi and Rutter, 2002). We have previously noted robust glucose-dependent differences between the mechanisms of b-cell death with respect to the involvement of notch signaling, netrin signaling, carboxypeptidase E, ATP-citrate lyase, Uchl1 and intracellular Ca 2+ release channels (IP3R, RyR) (Chu et al, 2012; (A,B) Mouse b-cells carrying a caspase-3 sensor were stained with Hoechst, PI and AlexaFluor647-conjugated annexin V. Cells were treated with the indicated treatments under 5 mM (A) and 20 mM glucose (B) and imaged for 60 hours at 37˚C and 5% CO 2. The absolute time for the onset of plasma membrane blebbing, nuclear condensation, caspase-3 activation, annexinV incorporation, PI incorporation and protein loss were determined (n515-63, mean6s.e.m., * P,0.05 compared with 5 mM glucose).…”
Section: Discussionmentioning
confidence: 99%
“…S2), presumably as a consequence of hyperglycemia, 27 signals released from apoptotic cells 28 and/or suppression of the antiproliferative activity of UCHL1 in β-cells. 8 Therefore, the hypothesis that UCHL1 deficiency enhances vulnerability of hIAPP-expressing β-cells to ER stress and apoptosis is supported, confirming a key role of the ubiquitin/ proteasome pathway in defense of β-cells from misfolded proteins.…”
Section: Deficiency In Uchl1 Leads To β-Cell Apoptosis In Hiapp Transmentioning
confidence: 77%
“…[7][8][9][10][11][12][13][14][15] Both of these protein degradation pathways are compromised in β-cells in T2DM. 9,15 We recently reported that polyubiquinated proteins accumulate in β-cells in T2DM, also noted in β-cells of rodents with high expression of amyloidogenic hIAPP but not soluble rodent-IAPP.…”
Section: Introductionmentioning
confidence: 99%